A Comparison of Fiqih on Profit Sharing of Investments in the Agricultural Sector - Prasetio, Andri; Setiawan, Iwan; Jubaedah , Dedah (Yayasan Mentari Madani, 2025)
This article explains the Muzara'ah, Mukhabarah, and Musaqah contracts. These are forms of agricultural cooperation that have existed since ancient times. In practice, the current collaboration between landowners and cultivators is commonly referred to as paroan sawah (rice paddy), where the contract is not written but only verbal. This often results in losses due to the lack of authentic evidence. In Islamic banking, the most widely used principles are musyawarah and mudharabah. Muzara'ah is specifically used by some Islamic banks for plantation or agricultural financing. Muzara'ah originates from the concept of